Age model of sediment core PS97/085-3 - Loftfield, Julia; Nowaczyk, Norbert R; Lembke-Jene, Lester; Frederichs, Thomas; Lachner, Johannes; Lamy, Frank; Rugel, Georg; Stübner, Konstanze; Adolphi, Florian
Age model of PS97/085-3 28 – 58 ka BP. Model is based on correlating relative paleointensities and magnetic inclination with the Black Sea core stack of Wu et al. (2021), on the correlation of XRF scan derived ln(Ca/Ti) to EDC temperature anomalies (AICC2023), and on the correlation of ln(Ca/Ti) and grain size to δ18O of EDML (AICC2023). The model is an update of the one of Wu et al. (2021).